Nebular Models of Sub-Chandrasekhar Mass Type Ia Supernovae: Clues to the Origin of Ca-rich Transients - Polin, Abigail; Nugent, Peter; Kasen, Daniel (The Astrophysical journal, 2021)
We use non-local thermal equilibrium radiative transport modeling to examine observational signatures of sub-Chandrasekhar mass double detonation explosions in the nebular phase. Results range from spectra that look like typical and subluminous Type Ia supernovae (SNe) for higher mass progenitors to spectra that look like Ca-rich transients for lower mass progenitors. This ignition mechanism produces an inherent relationship between emission features and the progenitor mass as the ratio of the nebular [Ca ii]/[Fe iii] emission lines increases with decreasing white dwarf mass. Examining the [Ca ii]/[Fe iii] nebular line ratio in a sample of observed SNe we find further evidence for the two distinct classes of SNe Ia identified in Polin et al. by their relationship between Si ii velocity and B-band magnitude, both at time of peak brightness. This suggests that SNe Ia arise from more than one progenitor channel, and provides an empirical method for classifying events based on their physical origin. Furthermore, we provide insight to the mysterious origin of Ca-rich transients. Low-mass double detonation models with only a small mass fraction of Ca (1%) produce nebular spectra that cool primarily through forbidden [Ca ii] emission.